A Covalent Calmodulin Inhibitor as a Tool to Study Cellular Mechanisms of K-Ras-Driven Stemness - Okutachi, Sunday; Manoharan, Ganesh Babu; Kiriazis, Alexandros; Laurini, Christina; Catillon, Marie; McCormick, Frank; Yli-Kauhaluoma, Jari; Abankwa, Daniel (Frontiers in Cell and Developmental Biology, 2021)
Recently, the highly mutated oncoprotein K-Ras4B (hereafter K-Ras) was shown to drive cancer cell stemness in conjunction with calmodulin (CaM). We previously showed that the covalent CaM inhibitor ophiobolin A (OphA), can potently inhibit K-Ras stemness activity. However, OphA a fungus derived natural product, exhibits an unspecific, broad toxicity across all phyla. Here we identified a less toxic, functional analogue of OphA that can efficiently inactivate CaM by covalent inhibition. We analyzed a small series of benzazulenones, which bear some structural similarity to OphA and can be synthesized in only six steps. We identified the formyl aminobenzazulenone 1, here named Calmirasone1, as a novel and potent covalent CaM inhibitor. Calmirasone1 has a 4-fold increased affinity for CaM as compared to OphA and was active against K-Ras in cells within minutes, as compared to hours required by OphA. Calmirasone1 displayed a 2.5 – 4.5-fold higher selectivity for KRAS over BRAF mutant 3D spheroid growth than OphA, suggesting improved relative on-target activity. Importantly, Calmirasone1 has a 40 – 260-fold lower unspecific toxic effect on HRAS mutant cells, while it reaches almost 50% of the activity of novel K-RasG12C specific inhibitors in 3D spheroid assays. Our results suggest that Calmirasone1 can serve as a new tool compound to further investigate the cancer cell biology of the K-Ras and CaM associated stemness activities.